Prevalence and Reproduction of Varroa and Tropilaelaps in Three Species of Honey Bees in Chiang Mai, Thailand - Ninat Buawangpong (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Apis mellifera was anthropogenically introduced to Southeast Asia with the goal of developing a commercial beekeeping industry based on this non-adapted species. Such regional approaches often neglect the potential problems of indigenous parasites and pathogens for the introduced species. Such has been the case when Asian honey bee brood mites quickly took 'advantage' of the presence of A. mellifera, a honey bee species adapted to temperate environments. Today the Asian honey bee brood parasites Varroa and Tropilaelaps are considered to be the most serious acarine pests for A. mellifera colonies in Thailand and throughout Southeast Asia. The giant honey bee (Apis dorsata) is the adapted host of Tropilaelaps spp. and the eastern honey bee (Apis cerana) is the indigenous host of two Varroa species. Some life history information concerning these brood parasites are available and much are based on studies utilizing A. mellifera hosts. However, none of these previous research efforts studied the host preference of T. mercedesae in its adapted host (A. dorsata), population fluctuation and reproduction of both mite genera in concurrently infested A. mellifera colonies, differential reproduction of Varroa haplotypes, and the impact of T. mercedesae on infested hosts.